Compressive behavior of Co-Cr-Mo radially graded porous structures under as-built and heat-treated conditions (Fracture and Structural Integrity, 2022)
Additive manufacturing research is continuously growing, and this field requires a full improvement of the capability and reliability of the processes involved. Of particular interest is the study of complex geometries production, such as lattice structures, which may have a potentially huge field of application, especially for biomedical products.In this work, the powder bed fusion technique was utilized to manufacture lattice structures with defined building angles concerning the build platform. A biocompatible Co-Cr-Mo alloy was used. Three different types of elementary cell geometry were selected: Face Centered Cubic, Diagonal, and Diamond. These cells were applied to the radially oriented lattice structures to evaluate the influence of their orientation in relation to the sample and the build platform. Moreover, heat treatment was carried out to study its influence on microstructural properties and mechanical behavior. Microhardness was measured, and compressive tests were performed to detect load response and to analyse the fracture mechanisms of these structures.The results show that the mechanical properties are highly influenced by the cell orientation in relation to the building direction and that the properties can be further tuned via HT. The favorable combination of mechanical properties and biocompatibility suggests that Co-Cr-Mo lattices may represent an optimal solution to produce customized metal implants.
Keywords: Selective Laser Melting (SLM); CoCrMo alloy; Radially graded lattice structure; Compressive test; Microstructure; Fracture analysis